2006 International Electron Devices Meeting 2006
DOI: 10.1109/iedm.2006.346883
|View full text |Cite
|
Sign up to set email alerts
|

A Screening Methodology for VMIN Drift in SRAM Arrays with Application to Sub-65nm Nodes

Abstract: SRAMs are an integral part of system on chip devices. With transistor and gate length scaling to 65nm/45nm nodes, SRAM stability across the product's lifetime has become a challenge. Negative bias temperature instability, defects, or other phenomena that may manifest itself as a transistor threshold voltage (V T ) increase can result in VMIN drift of SRAM memory cells through burn-in and/or operation. A direct assessment at time-zero is difficult because the transistor V T has not yet shifted, and therefore no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…These marginal transistors did not degrade static write margin due to the negligible sensitivity of the margin to variability in (Table I). Voltage screen tests such as described in [16] are commonly used to screen out defects and early failures in SRAM arrays. Such tests are usually carried out in-line at wafer sort using testers running at lower frequencies than actual operating frequencies.…”
Section: A Pulse Generatormentioning
confidence: 99%
“…These marginal transistors did not degrade static write margin due to the negligible sensitivity of the margin to variability in (Table I). Voltage screen tests such as described in [16] are commonly used to screen out defects and early failures in SRAM arrays. Such tests are usually carried out in-line at wafer sort using testers running at lower frequencies than actual operating frequencies.…”
Section: A Pulse Generatormentioning
confidence: 99%
“…Flipping SRAM cell data periodically removes stress and recovers the degraded SNM. Ball et al [17] developed a screening methodology for drift in SRAM arrays. Measured results showed that NWELL body bias control increases the likelihood of fails coming from lowered SNM.…”
Section: Introductionmentioning
confidence: 99%
“…Vmin fails have become the dominant memory fail mechanism throughout the product life cycle [1,2]. To maintain acceptable yields added SRAM redundancy is recommended.…”
Section: Introductionmentioning
confidence: 99%